The long non-coding RNA GAS5 contributes to the suppression of inflammatory responses by inhibiting NF-κB activity - Curci, Debora; Stankovic, Biljana; Kotur, Nikola; Pugnetti, Letizia; Gasic, Vladimir; Romano, Maurizio; Zukic, Branka; Decorti, Giuliana; Stocco, Gabriele; Lucafò, Marianna; Pavlovic, Sonja (Frontiers in Pharmacology, 2024)
Introduction Nuclear factor kappa B (NF-κB) is a key regulator of immune and inflammatory responses. Glucocorticoid drugs (GC) act through the glucocorticoid receptor (GR) as immunosuppressant also in pediatric patients inhibiting NF-κB activity. The long non-coding RNA GAS5 interacts with the GR, influencing GC activity. No data on the role of GAS5 on GR-dependent inhibition of NF-κB activity have been published. Methods This study investigated the impact of GAS5 on NF-κB activity in HeLa cells overexpressing GAS5, both under basal conditions and during GC treatment. The study used EMSA, RNA-immunoprecipitation (RIP), Western blotting, and bioinformatic analyses to assess NF-κB DNA binding, GAS5-p65 interaction, and NF-κB signaling pathway modulation. Results GAS5 overexpression increased NF-κB DNA binding activity in untreated cells. RNA-IP confirmed a direct interaction between GAS5 and the NF-κB subunit p65, suggesting a potential regulatory mechanism. GAS5 overexpression led to downregulation of NF-κB target genes, TNF-α, and NR3C1. GC treatment reduced NF-κB DNA binding activity in GAS5-overexpressing cells, indicating a potential synergistic effect. Furthermore, GAS5 overexpression increased IκB levels and reduced p-p65/pan-p65 levels during GC treatment. Discussion GAS5 appears to modulate NF-κB activity in a complex manner, influencing both basal and GC-induced signaling. The interaction between GAS5, GCs, and NF-κB is multi-faceted, and further research is needed to fully elucidate the underlying mechanisms. These findings suggest that GAS5 could be a potential target for personalized therapy, particularly in pediatric patients with inflammatory conditions.